Agents and professionalisation: improvement on the Egremont estates c.1770 to c.1860 - Webster, Sarah Ann (2011)
This thesis examines aspects of estate improvement on the Egremont estates in Sussex, Yorkshire and Australia between 1770 and 1860. Using the Petworth House Archives and others, it documents large-scale improvement projects, including William Smith’s work in mineral prospecting in West Yorkshire, and Colonel Wyndham’s land speculation in South Australia. The third Earl of Egremont (1751-1837) himself has received some biographical attention, but this has concentrated to a great extent on his patronage of the arts. This thesis therefore documents a number of important matters for the first time, in particular the detailed work of the middle layer of personnel involved in estate management and improvement. Episodes of ‘failure’ in estate improvement are also revealing in this study. This thesis contributes to debates regarding the nature of ‘improvement’ in this period, and most particularly, to understandings of the developing rural professions and to scholarship regarding professionalisation; interpreting key episodes in the archive utilising a ‘landscape’ approach. It uses the concept of an ‘estate landscape’ to draw together the dispersed Egremont estates in order to better understand the management structures of these estates, and how they relate to the home estate at Petworth.The thesis examines the relationships between Lord Egremont and the various agents (in the widest sense) who acted on his behalf; the configuration of which agents was different for each of the different estates. It makes a particular contribution to ongoing debates about the formation of the professions in eighteenth and nineteenth-century England in suggesting that despite the contemporary stress on applied agricultural expertise, legal land agents remained more influential than has been supposed. The belated professionalisation of the Petworth agents and the significant differences in their roles when compared with a land agency firm such as Kent, Claridge and Pearce suggests that estate management was far more diverse than has been suggested. Egremont himself emerges from the archive as neither a hands-on agricultural improver nor as an uninterested and neglectful absentee. Instead, I suggest, he acted as co-ordinator and as an impresario amongst the men engaged to act on his behalf, the middle layer of developing rural professionals including agents, surveyors, and engineers. If the literature to date has concentrated on Egremont as patron of art, he emerges from this thesis as a patron of improvement.